ANALISIS PENGGUNAAN METODE QIRA’ATI SEBAGAI INOVATIF DALAM PEMBELAJARAN AL-QURAN DI BUMRUNGSUKSA ISLAMIC BOARDING SCHOOL HATYAI, THAILAND - Azmi Prayogi; Hasrian Rudi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of the Qiroati method in the Qur'an learning process at Bumrungsuksa Islamic Boarding School Hatyai, Thailand. This study uses a qualitative approach with a case study design to obtain an in-depth overview of ongoing teaching practices. The research data sources consist of primary data obtained through direct observation of the learning process and interviews with teachers and students, as well as secondary data in the form of school documents and Qiroati method guidelines. Data collection techniques include observation, interviews, and documentation. The stages of data collection, data reduction, data presentation, and drawing conclusions are used in data analysis. The research findings indicate that the skills of the ustadz, the students' willingness to learn, and the availability of adequate learning materials all contribute to the successful implementation of the Qiroati method. This approach has been proven to help students read the Qur'an more accurately, especially in terms of makharijul huruf and tajwid..